College tutors perceptions of the source of bias in teaching practice assessment in Zimbabwe - Jeko, Ishmael; Mangwaya, Ezron (Midlands State University, 2014)
This study examines the source of bias in teaching practice assessment. Following a descriptive survey design, the researchers utilized a questionnaire to solicit views of a random sample of fifty-one college tutors working in three primary teacher training colleges in Zimbabwe. College tutors generally regard bias as highly prevalent in teaching practice assessment. In specific terms, college tutors routinely deviate from criteria of assessment as indicated on schedules of assessment, privileging factors entirely irrelevant to teaching effectiveness. It also came to light that inexperienced tutors tend to be particularly prone to bias when assessing teaching practice. The study recommended team assessment whereby more experienced tutors work with their less experienced counterparts as a way of mitigating bias in assessment of teaching practice. Additionally, the study calls for fostering continuous dialogue among college tutors on the interpretation of criteria of teaching practice assessment through seminars and workshops.